2017
DOI: 10.1111/asej.12124
|View full text |Cite
|
Sign up to set email alerts
|

Input Rigidities and Performance of Vietnamese Universities

Abstract: Universities in Vietnam are inclined to have an inefficient mix of input resources because of rigidities restricting the adoption of advanced teaching technology. There has been a deferral of the adoption of new teaching technologies to meet the rest of the world's higher education standards. Using an input‐orientated data envelopment analysis (DEA) method, technical, scale and mix efficiency indicators are estimated for 112 Vietnamese universities over the period 2011–2013 using the Färe–Primont index. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Sullivan et al (2012) asserted that enrolments and completions have been shown to be important in labour market studies and thus omitting one can miss a critical output dimension. Therefore, these variables should be considered as outputs in assessing the performance of TEIs, which are consistent with Cabanda (2007a, 2007b) Tran and Villano (2015, 2017a, 2017b, 2017c, 2017d, 2018.…”
Section: Input and Output Variablesmentioning
confidence: 85%
See 1 more Smart Citation
“…Sullivan et al (2012) asserted that enrolments and completions have been shown to be important in labour market studies and thus omitting one can miss a critical output dimension. Therefore, these variables should be considered as outputs in assessing the performance of TEIs, which are consistent with Cabanda (2007a, 2007b) Tran and Villano (2015, 2017a, 2017b, 2017c, 2017d, 2018.…”
Section: Input and Output Variablesmentioning
confidence: 85%
“…Operating costs were annually spent for TEIs' operations including teaching staff wages, student allowances, learning facility purchases, and other related academic costs. These input variables were also used in recent studies such as de Franca, de Figueiredo, and Lapa (2010), Miranda, Gramani, and Andrade (2012), Nguyen et al 2015, Tran and Villano (2015, 2017a, 2017b, 2017c, 2017d, 2018.…”
Section: Input and Output Variablesmentioning
confidence: 99%
“…Although research universities have the potential to exhibit high performance, this does not guarantee efficient use of their resources. Moreover, the efficiency of research universities may vary according to institutional ownership (Casani et al, 2014;Kao and Pao, 2009;Tran and Villano, 2017). Future research could include all universities in T€ urkiye and compare the efficiency of normal universities and research universities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the efficiency of research universities may vary according to institutional ownership (Casani et al. , 2014; Kao and Pao, 2009; Tran and Villano, 2017). Future research could include all universities in Türkiye and compare the efficiency of normal universities and research universities.…”
Section: Discussionmentioning
confidence: 99%
“…From the best of our knowledge this is the first study to analyse total factor productivity growth in South African higher education, and by doing so, we add to the limited studies in this area in developing and emerging economies using advanced TFP index methods such as Färe–Primont index (Tran & Villano, 2017 ). Majority of existing studies in this area have largely focussed on developed economies (see, Witte & López-Torres, 2017 for review) and are limited to the application of Malmquist-based index approach (e.g., Agasisti & Johnes, 2009 ; Flegg & Allen, 2007 ; Worthington & Lee, 2008 ) and Törnqvist index approaches (e.g., Moore et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%